EFEKTIFITAS PENGELOLAAN BUDAYA ORGANISASI STUDI KASUS DI BANK SENTRAL - Widyo Gunadi; Muliaman D. Hadad; Eriyatno Eriyatno; Parulian Hutagaol (School of Business, Bogor Agricultural University (SB-IPB), 2011)
The aim of this research is to develop a situational analysis of organization culture (OC). The analysis cover management process and its changing in Central Bank, including direction and substance of OC, developing ideal models, methods, dynamic change and its management. Awareness about the importance of OC in improving the performance of the organization had been recognized by management of The Central Bank in the surface, but when examined the dynamics of the changes, the implementation seem fluctuated.During this research, the values which adopted for this organization are competence, integrity, transparency, accountability, and cohesiveness. In the implementation, there are two main issues: (1) the belief that these values are match with organization need and (2) misunderstanding in implementation at the level of units. Research has not attempt to answer the solution of these two main issues yet. However, this study try to uncover the main problem of changes in OC. This paper using combination of several methods: survey, focus group discussion (FGD), statistics of secondary data, and structured in depth interviews. This study have found that The Central Bank conduct rapid change in the beginning of transformation. However, after 3 years, the change slow down, reducing the commitment and lack of confident both the substance of OC and the change method as well. Keywords: Organization Culture, Central Bank, Situational Analysis